An investigation of vocabulary knowledge on students' writing performance - Andi Samsidar; Rizki Fauzi; K Sharmila; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2022)
The aim of the research is finding out the level of the student’s vocabulary knowledge, the level of the students writing performance, and the correlation of vocabulary knowledge on students’ writing performance. The data source in this research were the students who were studying English at Muallimin Muhammadiyah Senior High School in Makassar, South Sulawesi, Indonesia. To obtain the data in the field, the researchers distributed writing and vocabulary test. This research found that the level of the students’ vocabulary knowledge is categorized as “good” classification. Most of students of Muallimin Muhammadiyah Senior High School Makassar got score 70 – 79 with the mean score is 66.84. This research also found that the level of the students’ writing performance is categorized as “fair” classification. Most of students of Muallimin Muhammadiyah Senior High School Makassar got score 60 – 69 with the mean score is 69.28. Finally this research revealed that there was a significant and positive correlation between students’ vocabulary knowledge and writing competence.